Structural integrity—Searching the key factor to suppress the voltage fade of Li-rich layered cathode materials through 3D X-ray imaging and spectroscopy techniques. (October 2016) - Xu, Yahong; Hu, Enyuan; Yang, Feifei; Corbett, Jeff; Sun, Zhihong; Lyu, Yingchun; Yu, Xiqian; Liu, Yijin; Yang, Xiao-Qing; Li, Hong
Abstract: Li-rich layered materials are important cathode compounds used in commercial lithium ion batteries, which, however, suffers from some drawbacks including the so-called voltage fade upon electrochemical cycling. This study employs novel transmission X-ray microscopy to investigate the electrochemical reaction induced morphological and chemical changes in the Li-rich Li2 Ru0.5 Mn0.5 O3 cathode particles at the meso to nano scale. Combined X-ray spectroscopy, diffraction and microscopy experiments are performed to systematically study this cathode material's evolution upon cycling as well as to establish a comprehensive understanding of the structural origin of capacity fade through 2D and 3D fine length scale morphology and heterogeneity change of this material. This work suggests that atomic manipulation (e.g. doping, substitution etc.) or nano engineering (e.g. nano-sizing, heterogeneous structure) are important strategies to mitigate the internal strain and defects induced by extensive lithium insertion/extraction. It also shows that maintaining the structural integrity is the key in designing and synthesizing lithium-rich layered materials with better cycle stability. Graphical abstract: Highlights: Direct observation of chemical and morphological heterogeneity of Li2 Ru0.5 Mn0.5 O3 cathode at particle level. Correlates the cathode material's meso/nano scale heterogeneity to its voltage fade. Understanding of the meso/nano scale morphology's impact on the electro-chemical reaction pathway.